Bioactive CaTiO₃ film prepared on the biomedical porous Ti-15Mo alloy by one-step hydrothermal treatment - Lai, T. (2021)
The bioactive CaTiO3 film was grown on the surface of the microwave sintered porous Ti–15Mo alloy by one-step hydrothermal process in supersaturated Ca(OH)2 solution. The microstructures of the film and apatite-forming ability and cytocompatibility of the hydrothermally treated porous Ti–15Mo alloy were then investigated. The results show that the hydrothermally treated sample has a thickness of approximately 250 nm and is mainly composed of CaTiO3 phase with some –OH groups except the α-Ti and β-Ti phases. The porous structure of the Ti–15Mo alloy has no significant change after hydrothermal treatment. When immersed in SBF solution, the hydroxyapatite preferentially nucleates and grows on the inner surface and the pore sites, forming a layer of the calcium-deficient apatite on the surface of the hydrothermally treated porous Ti–15Mo alloy finally. The hydrothermal treatment is demonstrated to facilitate the proliferation of MG-63 cells over the porous Ti–15Mo alloy surface (p < 0.01), and promote the alloy from Grade 1 of non-toxic material to Grade 0.